2021
DOI: 10.3390/ijerph18189622
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Child and Adolescent Mental Health Policy and Practice Implementation

Abstract: Background: The impact of the 2019 coronavirus pandemic on the mental health of millions worldwide has been well documented, but its impact on prevention and treatment of mental and behavioral health conditions is less clear. The COVID-19 pandemic also created numerous challenges and opportunities to implement health care policies and programs under conditions that are fundamentally different from what has been considered to be usual care. Methods: We conducted a qualitative study to determine the impact of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…Similar evidence has been reported by the qualitative study conducted by Palinkas and colleagues in the USA [165]: they interviewed 29 State Mental Health Authorities (SMHA) to determine the impact of the COVID-19 pandemic on the implementation of evidence-based policy and practice. The percentage of states reporting positive outcomes with telehealth implementation ranged from 80% to 100%, desire to continue the use of telehealth in the post-pandemic period ranged from 60% to 100%.…”
Section: The Role Of Telemedicine For the Mental Health Of Young Peop...supporting
confidence: 59%
“…Similar evidence has been reported by the qualitative study conducted by Palinkas and colleagues in the USA [165]: they interviewed 29 State Mental Health Authorities (SMHA) to determine the impact of the COVID-19 pandemic on the implementation of evidence-based policy and practice. The percentage of states reporting positive outcomes with telehealth implementation ranged from 80% to 100%, desire to continue the use of telehealth in the post-pandemic period ranged from 60% to 100%.…”
Section: The Role Of Telemedicine For the Mental Health Of Young Peop...supporting
confidence: 59%
“…Another reason for low interactions, some studies that surveyed physicians about their perspective on telehealth during the pandemic showed that they were concerned about the following: technological barriers, diagnostic reliability, cultural and social factors, lack of face-to-face interactions, and lack of a clear telemedicine legal framework. In addition, physicians tend to use WhatsApp ® and Zoom more than the "Sehha" app [50,70,71]. Therefore, more campaigns targeting the eligibility of these mHealth apps are suggested to increase awareness about their use [23].…”
Section: Major Findingsmentioning
confidence: 99%
“…Data from the Republic of Ireland [ 9 ] indicate that referrals to specialized child and adolescent mental health services dropped by around 10% up to August 2020 and then steadily increased up to December 2020, reaching 180% compared to previous years, with double the number of outpatient appointments compared to previous years. A recent qualitative U.S. study reported that services suspected an increased need for mental health care for children and young people during the pandemic, but that staff shortages and decreased service capacity under COVID-19 conditions made it difficult to estimate the true amount [ 10 ]. Another U.S. study analyzed admission to a child and adolescent psychiatry inpatient unit between March 2020 and January 2021 and found that 53% of admissions due to adolescent psychiatric crises were related to COVID-19 stressors, although the overall number of admissions had slightly decreased [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…As another effect of the pandemic, the implementation of telemental health increased, although a number of barriers were identified, such as unclear funding for services, limited internet access, family/client reluctance, or problems linked to online sessions with younger children [ 10 ]. A Canadian survey of mental health professionals working in services for mentally ill children and adolescents found that 71% of respondents began to use virtual care during pandemic.…”
Section: Introductionmentioning
confidence: 99%